Genotypic and phenotypic variability among morphological traits of Aquilaria malaccensis Lam. Genetic resources - Mohamed, M.B. Noor; Parthiban, K.T.; Ravi, R. (Indian Journal of Agroforestry, 2020)
Aquilaria malaccensis Lam. wood is principal source of agarwood (Gaharu), one of the most valuable forest products traded internationally. A nursery experiment was laid out in CRD by using seeds collected from 22 provenances in 3 states of North-Eastern hill regions of India. Seedling morphometric trait were measured and subjected to genotypic and phenotypic variability studies to ascertain their possibility of this species for future tree improvement. Genotypic coefficients of variability were less than phenotypic coefficient of variability. Maximum variability was observed for root/ shoot ratio (23.05) followed by sturdiness quotient (22.54) and plant height (21.57). Collar diameter (0.857) recorded minimum GCV value. Number of branches (36.93) had registered maximum PCV followed by root/shoot ratio (27.81) and sturdiness quotient (24.06). Shoot length (23.38) expressed moderate PCV followed by volume index (23.19). Collar diameter (2.376) had lowest PCV value followed by root length (9.841). High heritability was observed for sturdiness quotient (0.877) followed by plant height (0.851) and volume index (0.732). Low heritability was expressed by collar diameter (0.130) followed by number of branches (0.187) and root length (0.343). The estimate of genetic advance in percentage mean varied from 43.52% to 0.637%. Minimum genetic advance was estimated for collar diameter (0.637%) and maximum for sturdiness quotient (43.52%) followed by plant height (41.01%). For rest of the characters, genetic advance was moderate to low. This study reveals that wide ranges of variability among the provenance for the various traits were recorded.